2022
DOI: 10.4018/ijebr.293292
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Customer Relationship Management (E-CRM) and Customer Loyalty

Abstract: This study examined the impact of E-CRM on customer loyalty with the mediating effect of customer satisfaction in the banking industry. Customer satisfaction is important for loyalty because when the customers are satisfied with the services offered by their service providers, the relationship gets stronger which further leads to positive word-of-mouth. The data was collected using purposive sampling from 836 banks’ customers who were using E-CRM services and the data was analyzed using structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…The next hypothesis was also confirmed through both obtained data [0.358, 7.041], and indicated customer loyalty's significant and positive influence on the effectiveness of sustainable CRM in online shopping. These results are consistent with Shukla and Pattnaik [11], Al-Bashayreh and Almajali [4], and Kumar and Mokha [21]. The results emphasize the significance of customer satisfaction and loyalty as a contributor to the effectiveness of CRM in online shopping, while also correlating with other academics' and researchers' theories.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The next hypothesis was also confirmed through both obtained data [0.358, 7.041], and indicated customer loyalty's significant and positive influence on the effectiveness of sustainable CRM in online shopping. These results are consistent with Shukla and Pattnaik [11], Al-Bashayreh and Almajali [4], and Kumar and Mokha [21]. The results emphasize the significance of customer satisfaction and loyalty as a contributor to the effectiveness of CRM in online shopping, while also correlating with other academics' and researchers' theories.…”
Section: Discussionsupporting
confidence: 87%
“…It was shown that customer satisfaction acted as a mediator in the relationships between service quality and e-CRM system success, as well as between trust and e-CRM system success. [21] looked at the effect of E-CRM on client loyalty in the banking business, and the moderating impact of customer pleasure. The data were analyzed using AMOS and SEM.…”
Section: Research Backgroundmentioning
confidence: 99%
“…From the previous studies that the authors obtained, the majority of previous researchers associated e-CRM with loyalty, not commitment (Abu-Shanab & Anagreh, 2015;Irmal et al, 2020;Kumar & Mokha, 2022;Mulazid, 2018;D. R. Sari et al, 2021;N.…”
Section: The Effect Of E-crm On Customer Commitmentmentioning
confidence: 99%
“…al., 2018). Cognitive and emotional intermediary states and processes serve as an organism's -inner state representation and mediate the connections between the stimuli and a person's responses (Kumar, et. al., 2022).…”
Section: A Digital Finance Industry Framework For Banks and Financial...mentioning
confidence: 99%